IMPACT OF REGIONAL DISTRIBUTION AND AIR POLLUTION ON INTERNAL STRUCTURE OF MELIA AZEDARACH L. LEAVES - Abozaid, V.; Abdulrahman, H. Arif; Ibrahim, D. Ayoub (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was performed to investigate the impact of air pollution on leaf area and anatomical features of Melia azedarach L. trees, in urban areas with three demographical classes: location (I) industrial area, location (II) roadside area and free parts (control area) as a location (III) of Duhok city/Kurdistan Region-Iraq, during July 2021. The results demonstrated that the leaf area of selected plants' leaves in location I had reduced with no noticeable change in the average stomata density in the three locations I, II and Ⅲ. Meanwhile, the results of the most anatomical features of the blade (blade, lower cuticle, epidermis (both upper and lower) thickness, palisade layer height and spongy parenchyma width) in addition to midrib parameters (epidermis thickness (upper and lower), collenchyma and parenchyma layer width, phloem and xylem width and pith diameter) were decreased in both locations I, II, and with well-developed anatomical features in location III.